PENGARUH SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN DENGAN BRAND AWARENESS SEBAGAI VARIABEL MEDIASI PADA PSIS STORE - Ezza Fendiansyah Prayogo; Yoestini Yoestini (Diponegoro Journal of Management, 2022)
Indonesia is a multicultural country with a very large population. As a multicultural country with a large population, the public's interest in sports is also very large, especially in football. With the large public interest in football, almost all regions in Indonesia have teams or clubs that represent the regions, including the Semarang with its club, namely PSIS Semarang. As one of the biggest and most popular clubs in Indonesian football, PSIS Semarang has an official store that provides various merchandise from PSIS Semarang, PSIS Store. Along with the large population which is predicted to continue to increase and the increasing interest of the Indonesian people towards Indonesian football, the market opportunity for PSIS Store is very large. This research aims to confirm the influence of social media marketing variables on purchasing decision variables that have not been consistent, with brand awareness as a mediating variable. This research begins by developing a research model between social media marketing, brand awareness, and purchasing decisions. Data were obtained from 120 respondents who had filled out the questionnaire provided through the google form media. Respondents are consumers from the PSIS Store who have made at least two purchases and are at least 18 years old. Furthermore, the data that has been obtained were analyzed using Structural Equation Modeling (SEM) using analysis tool, the AMOS 26th version. The results of this research indicate that social media marketing has a significant positive effect on purchasing decisions, social media marketing has a significant positive effect on brand awareness, and brand awareness has a significant influence on purchasing decisions.